2022
DOI: 10.3390/agronomy12010158
|View full text |Cite
|
Sign up to set email alerts
|

Spring Precipitation Deficiency in Poland and Its Temporal and Spatial Variability in the Context of Agricultural Needs

Abstract: Deficient precipitation (dPr) in the growing season, especially in critical periods, affects plant condition and determines the quality and quantity of obtained yields. Knowledge about the variability and distribution of dPr is essential to mitigate its effect on agricultural soils and on crop and livestock production. The goal of the work is to determine the spatial and temporal distribution of spring precipitation deficiency and also to indicate the zones of risk and variability of its occurrence in Poland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
2
6
1
Order By: Relevance
“…Locations with similar climatic conditions may exhibit similar yield patterns and tuber structural characteristics. Similar observations regarding potato yield in different terrain conditions were made by Kalbarczyk & Kalbarczyk [56] and Pszczółkowski et al [58].…”
Section: Local Conditions and Yieldsupporting
confidence: 83%
See 2 more Smart Citations
“…Locations with similar climatic conditions may exhibit similar yield patterns and tuber structural characteristics. Similar observations regarding potato yield in different terrain conditions were made by Kalbarczyk & Kalbarczyk [56] and Pszczółkowski et al [58].…”
Section: Local Conditions and Yieldsupporting
confidence: 83%
“…Adding green light to red and blue light may increase chlorophyll content, photosynthesis, and production of smaller-sized tubers. A high proportion of red and blue light may increase tuber production, while adding green light may favor the production of smaller-sized tubers [55][56][57]. In summary, our research has shown the significant impact of potato varieties on yield and its quantitative characteristics.…”
Section: The Impact Of Varieties On Yield and Its Quantitative Charac...mentioning
confidence: 68%
See 1 more Smart Citation
“…Due to the fact that the Lublin region is a typically agricultural region, an increase in average precipitation totals -which was observed in our research from January to March -is beneficial from the viewpoint of meeting the precipitation needs of plants. It is un- Explanations: + p < 0.1, * p < 0.05, ** p < 0.01, *** p < 0.001 -significance level; P(mm) -average monthly precipitation total; cv(%) -coefficient of precipitation variability; Mann-Kendall (Z test) test -coefficient value of average monthly precipitation total trend; Sen's slope -increase/decrease of average monthly precipitation total in terms of 1 year favourable from the point of view of plant production that precipitation is not evenly distributed during the growing season -long periods of days without precipitation or an increase in the frequency of intensive precipitation can be observed (Pińskwar et al, 2019;Kalbarczyk and Kalbarczyk, 2022).…”
Section: Atmospheric Precipitation In the North-easternmentioning
confidence: 99%
“…These hazards are mainly linked to changes in precipitation; however, anthropogenic changes could intensify these problems (Kundzewicz et al 2005, Bryndal 2015, Boergens et al 2020). In addition, in the north of this region the Baltic Sea is located, and according to its characteristics, the Baltic sea region is sensitive to meteorological droughts as low ows could affect the quality of the Baltic Sea and its ecosystem (Kundzewicz 2009, Meier et Kalbarczyk and Kalbarczyk 2022). This study is novel in that it represents the rst comprehensive evaluation of precipitation concentration variability in a region of Central Europe using various indices, based on a gridded dataset.…”
Section: Introductionmentioning
confidence: 99%